(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The idea of using controllable relay nodes for designing mobile systems has been explored by several researchers. The main objective of this paper is to design a framework for deploying relay nodes with controlled mobility to conserve power in MANET. To meet out this proposal, a heterogeneous network consisting of traditional nodes with limited energy and relay nodes with more energy resources are considered. The deployment of relay nodes are based on the following two methods: 1. Min-Total, aims to minimize the total energy consumption of all the traditional nodes in the network. 2. Min-Max, aims to minimize the energy consumed by a traditional node in the network. The solution of these two methods can be used to prioritize each individual node in the network. The trade-offs involved in deploying an increasing/decreasing fraction of relay nodes, varying node weights, varying epoch duration is analyzed. This framework aims at dynamically combining both Min-Total and Min-Max based on the characteristics and requirements of the network.